2022
DOI: 10.1108/ijefm-02-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Sport fans' nostalgia and revisit intention to stadiums during the Covid-19 pandemic

Abstract: PurposeThis study aimed to examine how sport fans' nostalgia influenced their revisit intention to stadiums. Using data collected during the Covid-19 pandemic, the study further analyzed the moderation effect of sport fans' match attendance on the relationship between nostalgia and revisit intention.Design/methodology/approachThe study used an online survey querying baseball and football fans in Japan (n = 863). These leagues completed their 2020 regular season with and without crowds due to the pandemic. Nost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…From this, sport nostalgia is broken down into four dimensions, namely, experience (i.e., nostalgic feelings related to positive memories of the experience itself, sights, and environments in which sport takes place), socialization (i.e., nostalgia associated with past relationships with others at sporting events), personal identity (i.e., nostalgic feelings toward one's identity focusing on roles in sport), and group identity (i.e., nostalgia related to an individual's group experience, culture, and norm) [ 10 ]. Based on the four dimensions, researchers have developed nostalgia scales [ 22∗∗ , 23 , 24 , 25 ] and examined the various roles of nostalgia in sport and leisure [e.g., 18 , 26∗ , 27 , 28 , 29∗ , 30 , 31 ]. In other words, the multidimensional approach to nostalgia allowed researchers to investigate how it functions in sport and leisure.…”
Section: Sport Nostalgiamentioning
confidence: 99%
See 1 more Smart Citation
“…From this, sport nostalgia is broken down into four dimensions, namely, experience (i.e., nostalgic feelings related to positive memories of the experience itself, sights, and environments in which sport takes place), socialization (i.e., nostalgia associated with past relationships with others at sporting events), personal identity (i.e., nostalgic feelings toward one's identity focusing on roles in sport), and group identity (i.e., nostalgia related to an individual's group experience, culture, and norm) [ 10 ]. Based on the four dimensions, researchers have developed nostalgia scales [ 22∗∗ , 23 , 24 , 25 ] and examined the various roles of nostalgia in sport and leisure [e.g., 18 , 26∗ , 27 , 28 , 29∗ , 30 , 31 ]. In other words, the multidimensional approach to nostalgia allowed researchers to investigate how it functions in sport and leisure.…”
Section: Sport Nostalgiamentioning
confidence: 99%
“…In other words, sport nostalgia can be used as an effective strategic tool for improving brand equity and purchase intention, ultimately promoting consumption in the sport and leisure industries [ 19 , 35 , 36 ]. Furthermore, it can be applied in marketing strategies to increase individuals’ satisfaction and intention to consume in the future [ 8 , 18 , 21 , 31 ].…”
Section: Nostalgia As a Marketing Toolmentioning
confidence: 99%
“…With the gradual slowing down of the COVID-19 pandemic, studies on revisit intention of leisure sports in the post-pandemic era have taken on a different appearance, with more studies incorporating the COVID-19 pandemic theme. For example, [42] explored sports fans' nostalgia and revisit intentions to stadiums during the COVID-19 pandemic. The research results indicated that nostalgia for sports teams significantly influenced sports fans' intention to revisit stadiums.…”
Section: Revisit Intentionmentioning
confidence: 99%
“…Previous research has indicated that experience is a crucial element for trippers in increasing their contentedness and in reaching good behavior (H. Kim et al, 2015;Sie et al, 2021). Past travel experiences are a fount of personal information for destination choice, revisit intention, and WoM (Cho et al, 2020;Takata & Hallmann, 2022). The tourist experience is the notable driver of revisit intention (Hu & Shen, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Tourist loyalty is directly triggered by the satisfaction of tourists visiting tourist destinations. In various studies in the tourism industry that examine the behavior of returning tourists, satisfaction acts as an antecedent variable, and mediates the intention to revisit (Cho et al, 2020;Takata & Hallmann, 2022).…”
Section: Introductionmentioning
confidence: 99%